Effect Of Santri Model Training On Religiosity And Spiritual Care Of Nursing Students - ISNAWATI, IIN AINI (Sahabat Publikasi Kuu, 2026)
Introduction: Spiritual care is one of the nursing services in meeting the spiritual needs of patients and the components of spiritual care and religiosity are recognized as prerequisites for clinical capacity and competence. The current study determined the effect of santri model training on religiosity and spiritual care in nursing students. Methods: This pre-experimental study was conducted on 75 nursing students at Hafshawaty Zainul Hasan University in Probolinggo, Indonesia, who were selected through non random sampling. Data collection tools are religiosity scale and spiritual care questionnaire SCCS for nursing students. The data obtained were analysed with SPSS20 using descriptive and inferential statistics. Results: The mean scores of students religiosity and spiritual care before and after were 52,4 to 68 dan 89,3 to 119, respectively. The Wilcoxon test results p=0.00 < α 0,05 show that the santri model training has a positive and significant correlation with student religiosity and spiritual care. Conclusion The results showed that the higher the level of religiosity and clinical spiritual care, the more spiritual care competence will be developed. Thus, nursing educators and health system managers should provide santri model training to improve the religiosity and spiritual care in nursing to develop their spiritual care competencies.